Influence of metal bar lever-arm on screws detorque for dental prosthesis implant supported - Wilson MATSUMOTO; Ana Paula MACEDO; Rossana Pereira de ALMEIDA; Anselmo Agostinho SIMIONATO; Takami Hirono HOTTA (Universidade Estadual Paulista, 2021)
Abstract Introduction The cantilever length of implant-supported fixed prosthesis metal structure has been considered an important factor to transfer occlusion forces to the dental implant. Objective This study evaluated the influence of different extensions of cantilevers of Branemark protocol implant prosthesis when submitted to mechanical thermocycling by screw loosening evaluation. Material and method The groups G10 (n = 5), G15 (n = 5) and G20 (n = 5) were formed according to the distance in millimeters between the force application site in the cantilever and the center of the last implant. All metal structures (n = 15) were submitted to a 120 N cyclic vertical load in a chewing simulation machine (MSM-Elquip, São Carlos-SP, Brazil) under controlled temperature and moisture conditions. Two hundred and fifty thousand mechanical cycles were performed with a frequency of 2 Hz that simulates a masticatory activity similar to 3 months. To compare the data obtained regarding the loosening of the metal structure screws, implant position and sites of load application, the analysis of variance with two factors and the Tukey test were performed. Result Statistical analysis showed that the G10 group presented greater torque loss, statistically different from G15 (p = 0.001) and G20 (p = 0.002), and there was no significant difference between groups G15 and G20. Conclusion It can be concluded from the results that all the screws presented torque loss after simulation of 3 month masticatory activity, suggesting the need for periodical evaluation to prevent failures in the treatment.